COUNSELING AND MENTORING OF KAIZEN MANAGEMENT IMPLEMENTATION AT SRIJAYA CAR REPAIR SHOP SURABAYA - Yahya Yahya; Anton Eko Yulianto (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2021)
The purpose of community service activities (PKM) which is carried out through the activity of